Perancangan Aplikasi Pelacakan Program Kerja Kampus di STMIK Antar Bangsa - Subhiyanto; Aristejo; Esthi Adityarini (Jurnal Teknik Informatika, 2023)
Abstract— Every agency or company certainly has a work program for the next one year, this is also carried out at STMIK Antar Bangsa. However, with the passage of time, often during the evaluation, problems of incompatibility were found between the previously designed work programs and their implementation. To overcome this problem we propose a work program tracking application design (APELPROKER) using the waterfall method with the User Acceptance Test (UAT), testing technique which produces 93.75% of respondent responses with the aim of being able to help solve criteria problems very well.